Identification of fault locations in underground distribution system using Discrete Wavelet Transform - Ngaopitakkul, A.; Apisit, C.; Pothisarn, C.; Jettanasen, C.; Jaikhan, S. (My University, 2010)
In this paper, a technique for detecting faults in underground distribution system is presented. Discrete Wavelet Transform (DWT) based on traveling wave is employed in order to detect the high frequency components and to identify fault locations in the underground distribution system. The first peak time obtained from the faulty bus is employed for calculating the distance of fault from sending end. The validity of the proposed technique is tested with various fault inception angles, fault locations and faulty phases. The result is found that the proposed technique provides satisfactory result and will be very useful in the development of power systems protection scheme.
Keywords: ATP/EMTP; Fault location; Travelling wave; Underground cable; Wavelet transform